Expanded Insights Into Mechanisms of Gene Expression and Disease Related Disruptions - Smith, Moyra; Flodman, Pamela L. (Frontiers in Molecular Biosciences, 2018)
Definitive molecular diagnoses in disorders apparently due to genetic or genomic defects are still lacking in a significant number of investigated cases, despite use of studies designed to discover defects in the protein coding regions of the genome. Increasingly studies are being designed to search for defects in the non-protein coding genome, and for alterations in gene expression. Here we review new insights into genomic elements involved in control of gene expression, including methods to analyze chromatin that is accessible for transcription factor binding, enhancers, chromatin looping, transcription, RNA binding proteins and alternative splicing. We review new studies on levels of genome organization, including the occurrence of transcriptional domains and their boundary elements. Information is presented on specific malformation syndromes that arise due to structural genomic changes that impact the non- protein coding genome and sometimes impact specific transcriptional domains. We also review convergence of genome wide association with studies of gene expression, discoveries related to expression quantitative trait loci and splicing quantitative trait loci and the relevance of these to specific complex common diseases. Aspects of epigenetic mechanisms and clinical applications of analyses of methylation signatures are also discussed.